An analysis of the influences on the moving and handling practice of diploma student nurses within a medical environment - Abbott, Michael John (2002)
Anecdotal evidence indicates that in clinical practice diploma student nurses encounter M&H practices that do not always reflect those taught in training and that these influence their own practice. There is little available research evidence that identifies the factors that influence students moving and handling.